2018
DOI: 10.1073/pnas.1719168115
|View full text |Cite
|
Sign up to set email alerts
|

LSD1 activates a lethal prostate cancer gene network independently of its demethylase function

Abstract: Medical castration that interferes with androgen receptor (AR) function is the principal treatment for advanced prostate cancer. However, clinical progression is universal, and tumors with AR-independent resistance mechanisms appear to be increasing in frequency. Consequently, there is an urgent need to develop new treatments targeting molecular pathways enriched in lethal prostate cancer. Lysine-specific demethylase 1 (LSD1) is a histone demethylase and an important regulator of gene expression. Here, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
195
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(214 citation statements)
references
References 47 publications
(76 reference statements)
10
195
1
Order By: Relevance
“…39 In line with this model, recent reports in prostate cancer cell lines described a scaffolding role for KDM1A, whereby catalytically inactive KDM1A was still able to establish the prostate cancer gene network and ensure survival of castration-resistant prostate cancer cell lines. 40 This was further confirmed with the tool compound SP2509, proposed as an allosteric inhibitor binding to the H3 pocket region of KDM1A, capable of inducing cell death in prostate cancer cell lines. Similarly, this could also explain the previously observed reversal of the EWS-FL1 signature effects with SP2509 in Ewing sarcoma cells.…”
Section: Global or Promoter-specific Accumulation Of Methylation Of H3k4mentioning
confidence: 68%
“…39 In line with this model, recent reports in prostate cancer cell lines described a scaffolding role for KDM1A, whereby catalytically inactive KDM1A was still able to establish the prostate cancer gene network and ensure survival of castration-resistant prostate cancer cell lines. 40 This was further confirmed with the tool compound SP2509, proposed as an allosteric inhibitor binding to the H3 pocket region of KDM1A, capable of inducing cell death in prostate cancer cell lines. Similarly, this could also explain the previously observed reversal of the EWS-FL1 signature effects with SP2509 in Ewing sarcoma cells.…”
Section: Global or Promoter-specific Accumulation Of Methylation Of H3k4mentioning
confidence: 68%
“…Other coregulators of AR, such as lysine-specific histone demethylase 1A (LSD1), have been shown to have a reprogrammed activity in CRPCs, where it is also highly expressed (Liang et al 2017, Sehrawat et al 2018. Importantly, LSD1 has been shown to be one of the responsible factors for AR in castration-challenged PC cells (Cai et al 2011).…”
Section: The Androgen Receptor Drives Chromatin Relaxation As An Oncomentioning
confidence: 99%
“…Additionally, we observed that the half‐life of LSD1 is decreased from an initial 30 h to 21 h after HCI‐2509 treatment. This is in agreement with previous studies with respect to neuroblastoma and prostate cancer (Ambrosio et al ., ; Sehrawat et al ., ).…”
Section: Discussionmentioning
confidence: 97%